Prove that e is an irrational number.

Recall that $\,\mathrm{e}=\displaystyle\sum_{n=0}^\infty\frac{1}{n!},\,\,$ and assume $\,\mathrm{e}\,$ is rational, then

$$\sum\limits_{k=0}^\infty \frac{1}{k!} = \frac{a}{b},\quad \text{for some positive integers}\,\,\, a,b.$$


$$b\sum\limits_{k=0}^\infty \frac{1}{k!} =a$$


$$ b\left(1+1+\frac{1}{2} + \frac{1}{6} +\cdots \right)= a. $$

Where can I go from here?


5 Answers 5



We first show that $2<\mathrm{e}<3$ (see below), and hence $\mathrm{e}$ is not an integer.

Next, following up OP's thought, assuming $\mathrm{e}=a/b$, we multiply by $b!$ and we obtain $$ \sum_{k=0}^\infty \frac{b!}{k!}=a\cdot (b-1)! \tag{1} $$ The right hand side of $(1)$ is an integer.

The left hand side of $(1)$ is of the form $$ \sum_{k=0}^b \frac{b!}{k!}+\sum_{k=b+1}^\infty \frac{b!}{k!}= p+r. $$ Note that $p=\sum_{k=0}^b \frac{b!}{k!}$ is an integer, while $$ 0<r=\sum_{k=b+1}^\infty \frac{b!}{k!}=\frac{1}{b+1}+\frac{1}{(b+1)(b+2)}+\cdots<\sum_{k=1}^\infty \frac{1}{(b+1)^k}=\frac{1}{b}<1. $$

Note. The fact that $\mathrm{e}\in (2,3)$ can be derived from the inequalities $$ \left(1+\frac{1}{n}\right)^{\!n}<\mathrm{e}<\left(1+\frac{1}{n}\right)^{\!n+1}, $$ for $n=1$ for the left inequality and $n=5$ for the right inequality.

  • $\begingroup$ how did you get that p+r? $\endgroup$ Mar 15, 2014 at 19:03
  • 3
    $\begingroup$ @terribleatmath he merely named those two summations as $p+r$. Great solution, (+1) $\endgroup$
    – Guy
    Mar 15, 2014 at 19:07
  • 1
    $\begingroup$ ah right. can either of you guys explain to me why the first sum is an integer and the second is not? $\endgroup$ Mar 15, 2014 at 19:09
  • 2
    $\begingroup$ In the first sum, $k\leq b$ so $k!|b!$, so each term is an integer, so the sum is an integer. In the second sum, $k>b$, and it can be shown inductively that the sum is less than 1. $\endgroup$ Mar 15, 2014 at 19:19
  • $\begingroup$ Are there any other proofs that wouldn't be based on the same idea of multiplying by $b!$ ? Because most proofs I could find are just some variations of that. $\endgroup$ Jul 16, 2017 at 21:09

I like the following mild variant, which is less popular. Equivalently, we prove that $e^{-1}$ is irrational. Suppose to the contrary that $e^{-1}=\frac{m}{n}$ where $m$ and $n$ are integers with $n\gt 0$. We have $$e^{-1}=\sum_{k=0}^{n}\frac{(-1)^k}{k!}+\sum_{k=n+1}^\infty \frac{(-1)^k}{k!}.$$ Multiply through by $n!$. We get that $$n!\sum_{k=n+1}^\infty \frac{(-1)^k}{k!}$$ must be an integer.

However, by the reasoning that leads to the Alternating Series Test, we have $$0\lt \left|n!\sum_{n+1}^\infty \frac{(-1)^k}{k!}\right|\lt \frac{n!}{(n+1)!}\lt 1.$$

The (small) advantage is that the estimation of the tail is easier than when we use the series expansion of $e$.

  • 1
    $\begingroup$ I like this proof too! $\endgroup$
    – SiXUlm
    Feb 4, 2016 at 19:55

Here is yet another one, which is one of my favorite irrationality/transcendence proofs :

The confluent hypergeometreic series

$$_{0}F_{1}(k; z) = \sum_{n = 0}^\infty \frac1{(k)_n} \frac{z^n}{n!}$$

Satisfies the more-or-less easily verifiable identity

$$_0F_1(k-1;z) - {}_0F_1(k; z) = \frac{z}{k(k-1)}{}_0F_1(k+1;z)$$

Iterating this, one ends up with the continued fraction

$$\frac{{}_0F_1(k+1;z)}{k{}_0F_1(k;z)} = \frac1{k+\cfrac{z}{k+1+\cfrac{z}{k+2+\cfrac{z}{k+3+\cdots}}}}$$

Now note that $_0F_1(3/2;x^2/4) = \cosh(x)$ and $x \,{}_0F_1(3/2;x^2/4) = \sinh(x)$, hence applying the above one has the pretty well-known continued fraction

$$\tanh(x) = \cfrac{x/2}{\frac{1}{2} + \cfrac{\frac{x^2}{4}}{\frac{3}{2} + \cfrac{\frac{x^2}{4}}{\frac{5}{2} + \cfrac{\frac{x^2}{4}}{\frac{7}{2} + \cdots}}}} = \cfrac{x}{1 + \cfrac{x^2}{3 + \cfrac{x^2}{5 + \cfrac{x^2}{7 + \cdots}}}}$$

Note, however, that $$\tanh(x) = \frac{\exp(x) - \exp(-x)}{\exp(x) + \exp(-x)}$$ but since the continued fraction above is not finite, $\tanh(1)$ is not rational. Hence $e$ is not rational either.


While it may not lead to a better formal proof than other approaches, I find the following quite intuitive. It also compares nicely to Euler's original proof using the continued fraction representation of$~e$.

It is easy to see that every rational number $\alpha\in(0,1)_\Bbb Q$ can be uniquely expressed as $$\alpha = \frac{c_1}{1!}+\cfrac{c_2}{2!}+\cdots+\cfrac{c_k}{k!} \quad\text{with $k>1$, integers $0\leq c_i<i$ for $i=0,\ldots,k$, and $c_k\neq0$.} $$ One can interpret this as the expression of $\alpha$ in the fractional counterpart of the factorial number system. Writing this as $\alpha=(c_1,c_2,\ldots,c_k)_!$ ones has the familiar property of finite decimal representations (without integer part), that the order of two such numbers is given by lexicographic comparison of their representations $(c_1,c_2,\ldots,c_k)$.

Now $e-2$ is the limit of the rational numbers of the form $(0,1,\ldots,1)_!$ as the number of digits $1$ goes to infinity (the "$-2$" removes to two integral terms $\frac1{0!}$ and $\frac1{1!}$). Clearly this cannot converge to any number with a finite representation $(c_1,c_2,\ldots,c_k)_!$.

If one would want to turn this into a formal argument, one could argue as follows. Once the "digit" in position $k+1$ has become $1$, all further numbers in the sequence lie in the closed interval between the $k+1$ digit numbers $(0,1,\ldots,1,1)_!$ and $(0,1,\ldots,1,2)_!$, which interval does not contain any number with a $k$-digit representation $(c_1,c_2,\ldots,c_k)_!$, and in particular the sequence cannot converge to such a number.


Reading Courant-Robbins I was surprised to see that proving the irrationality of $$ e = \sum_{n=0}^{\infty} \frac{1}{n!} = 2 + \frac{1}{2} + \frac{1}{2 \cdot 3} + \frac{1}{2 \cdot 3 \cdot 4} + \dots $$ isn't harder than proving the irrationality of $\sqrt{2}$, just a bit more laborious (I fear that with $\pi$ things go in a very different way...). I found Courant-Robbins proof development very concise, so I developed the proof in 15 numbered steps (with the purpose to be more explicit and clear). In the first part of the proof (step $1\to 4$) we'll show that surely the first ten digit of $e$ are $2.718281828$ (for the second part of the proof it would be sufficient to prove that $e$ is not natural, but since we're playing, better do a good estimate). In the second part (step $5\to 15$) we'll focus on irrationality of $e$.

  • 1 ) We start proving a formula that we will use two times (step 4 and step 14): if $k$ is a natural number bigger than one, we have $$ \sum_{n=0}^{\infty} \frac{1}{k^n} = \frac{1}{1-\frac{1}{k}} $$ To prove this, let's consider the sum $$ G_n = q^0 + q^1 + q^2 + \ldots + q^n $$ Multiplying both member by $q$ we get $$ q G_n = q^1 + q^2 + q^3 + \ldots + q^{n+1} $$ and subtracting we get (suppose $q \neq 1$) $$ G_n = \frac{1-q^{n+1}}{1-q} $$ If $q=\frac{1}{k}$ with $k$ natural bigger than one, and if the sum goes to $n \to \infty$, the second term in the numerator goes to zero, qed.

  • 2 ) Summing first 13 terms of $\sum \frac{1}{n!}$ (i.e. from $n=0$ to $n=12$ inclusive) we find $$ \sum_{n=0}^{12} \frac{1}{n!} = \frac{260412269}{95800320}$$ that is about $2.71828182829$.

  • 3 ) The difference $\xi$ between this estimate and the true value of $e$ is $$ \xi = \frac{1}{13!} + \frac{1}{14!} + \frac{1}{15!} + \ldots = \frac{1}{13!} + \frac{1}{13!\cdot 14} + \frac{1}{13!\cdot 14 \cdot 15} + \ldots $$ We can overvalue in this way $$ \xi < \frac{1}{13!} + \frac{1}{13!\cdot 13} + \frac{1}{13!\cdot 13^2} + \ldots = \frac{1}{13!} \left( 1 + \frac{1}{13} + \frac{1}{13^2} + \ldots \right) $$ So $$ \xi < \frac{1}{13!} \sum_{n=0}^{\infty} \frac{1}{13^n} $$

  • 4 ) Using the formula proved in step 1 we have $$ \xi < \frac{1}{13!} \cdot \frac{1}{1-\frac{1}{13}} = \frac{1}{12! \cdot 12} = \frac{1}{5748019200} \approx 1,7 \cdot 10^{-10} $$ This means that the error due to the fact we stopped the sum to thirteenth term can influence at most the tenth digit after the dot (adding $0.00000000017$ to $2.71828182829$ we cannot change the first ten digit of the number). The first part of proof is ended: $e$ "starts" with $2.718281828$.

  • 5 ) Let's prove the irrationality of $e$ by supposing, by absurd, that it is rational: $$ e = \frac{p}{q} \qquad p,q \in \mathbb{N} $$

  • 6 ) We already proved that $e \approx 2.7$. In particular, $e \notin \mathbb{N}$, so $$ q \ge 2 $$

  • 7 ) Let's substitute in $e=\frac{p}{q}$ the definition of $e$ and let's multiply two member of this equation by $q!$ (on the right, I simplified $\frac{q!}{q}$ to $(q-1)!$) $$ \left( \frac{1}{0!} + \frac{1}{1!} + \frac{1}{2!} + \frac{1}{3!} + \ldots \right) q! = p (q-1) ! $$

  • 8 ) Let's rewrite the first member in a different way $$ \begin{array}{c} \displaystyle \left( 2 + \frac{1}{2!} + \frac{1}{3!} + \ldots \right. \\ \displaystyle \left. + \frac{1}{(q-2) !} + \frac{1}{(q-1) !} + \frac{1}{q!} + \frac{1}{(q+1) !} + \frac{1}{(q+2) !} + \ldots \right) q! \end{array} $$ Doing the product we have $$ 2 q! + 3 \cdot 4 \cdot \ldots \cdot q + 4 \cdot 5 \cdot \ldots \cdot q + \ldots + (q-1) \cdot q + q + 1 + \frac{1}{q+1} + \frac{1}{(q+1) (q+2) } + \ldots $$

  • 9 ) Let's define the number $A$, $B$ and $C$ in this way $$ A = p (q-1) ! $$ $$ B = 2 q! + 3 \cdot 4 \cdot \ldots \cdot q + 4 \cdot 5 \cdot \ldots \cdot q + \ldots + (q-1) \cdot q + q + 1 $$ $$ C = \frac{1}{q+1} + \frac{1}{(q+1) (q+2) } + \ldots $$

  • 10 ) Using the number $A$, $B$ and $C$, and exploiting step 8, the equation of step 7 can be written in this way $$ B + C = A $$

  • 11 ) $A$ e $B$ are clearly integer by definition, so if we prove that $C$ is not integer we have an absurdity starting by the hypothesis of rationality of $e$ and the proof is ended.

  • 12 ) The terms of the serie $\frac{1}{q+1} + \frac{1}{(q+1) (q+2) } + \ldots$ must be smaller (with the only exception of the first term) to the terms of the serie $$ \frac{1}{q+1} + \frac{1}{(q+1) ^2} + \ldots = \sum_{n=1}^{\infty} \frac{1}{(q+1) ^n} = \sum_{n=0}^{\infty} \frac{1}{(q+1) ^n} - 1 $$ So we certainly have $$ C < \sum_{n=0}^{\infty} \frac{1}{(q+1) ^n} - 1 $$

  • 13 ) The serie $\sum_{n=0}^{\infty} \frac{1}{(q+1) ^n}$ take the greatest possible value when the natural number $q$ take the smallest possible value. So we certainly have ( $q=1$ is excluded, as showed in step 6) $$ C < \sum_{n=0}^{\infty} \frac{1}{3^n} - 1 $$

  • 14 ) Exploiting the theorem proved in the step 1, the last inequality becomes $$ C < \frac{1}{1-\frac{1}{3}} - 1 = \frac{1}{2} $$

  • 15 ) We proved that $C<\frac{1}{2}$, so $C \notin \mathbb{N}$. Observing the step 11 we see that the proof is ended: $e$ is irrational.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.